CULTURAL BELIEFS AND DIETARY PATTERNS: UNDERSTANDING WOMEN’S FOOD CHOICES IN RURAL NORTHERN GHANA - Asare, Kwame Nii; Mensah , Abena Yaa (Ayden Journal of Agriculture and Allied Studies, 2025)
Low dietary quality represents a significant global public health challenge, particularly affecting children and women of reproductive age (WRA). It is a well-established risk factor for several major diseases, including maternal and child malnutrition, and non-communicable diseases. The dietary habits of women, especially during critical periods such as adolescence, conception, and lactation, directly influence both their own health and the well-being of their families. Consuming suboptimal diets compromises women’s health and their ability to nourish their households, notably the nutritional needs of young children. Maternal nutrition plays a crucial role in the health outcomes of children, making it vital to ensure women, particularly those in reproductive ages, have access to nutritious and balanced diets. Improving the dietary quality of women, especially in resource-limited settings, not only enhances their health status but also contributes to the broader improvement of household nutrition. This paper highlights the significance of enhancing women’s dietary quality, offering insight into the broader public health implications of addressing low dietary quality among women of reproductive age, with a particular focus on strategies that can optimize maternal health and nutrition in diverse settings.